Experimental study on heat and mass transfer during fast pyrolysis of biomass particle - Irii, T. (Trans Tech Publications Ltd, 2014)
Heat and mass transfer during fast pyrolysis of wood biomass in paying attention to the effects of the setting temperature TS and kind of biomass have been studied experimentally. From the time courses of the temperature at the center TC of a cornel particle, there could be two regions due to endothermic decomposition of biomass and exothermic tar cracking. Between these two regions, the decomposition of biomass could be completed at about 690 K. The exothermic behavior was observed at TS < 873 K. On the other hand, the maximum generated gas flow rate Gmax increased dramatically at TS > 773 K due to both the decomposition of biomass and the decomposition of generated tar. From the time courses of the temperature at the center TC of the fragment of perm kernel shell (PKS), the exothermic behavior was only observed. The maximum difference between the TC and the ambient temperature TA at the exothermic region was higher than that for the cornel particle. From the fact, the maximum gas flow rate was larger than that for the cornel particle. Â© 2014 Trans Tech Publications, Switzerland.